2021
DOI: 10.1177/21582440211006734
|View full text |Cite
|
Sign up to set email alerts
|

Status Quos Are Made to be Broken: The Roles of Transformational Leadership, Job Satisfaction, Psychological Empowerment, and Voice Behavior

Abstract: Employee voice behavior has attained significant attention in contemporary research due to its positive consequences for both workers and employers. Drawing on the social exchange theory, this study examined the mediating role of job satisfaction and psychological empowerment on the relationship between transformational leadership and employee’s voice behavior. Data were collected through survey questionnaires by utilizing a three-wave time-lagged study design from employees from diverse private and public sec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3

Relationship

3
6

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 108 publications
3
21
0
Order By: Relevance
“…The fit statistics for the 5-factor model and the 3-factor model had an acceptable fit (Hair et al, 2014) and showed to be better than the alternate 1-factor model (Table 2). Moreover, the fit statistics were consistent with the recent study by Ilyas et al (2021). However, we chose the 3-factor model, as it supports the conceptual and operational definitions of the constructs used for empirical analysis.…”
Section: Confirmatory Factor Analysis (Cfa)supporting
confidence: 56%
“…The fit statistics for the 5-factor model and the 3-factor model had an acceptable fit (Hair et al, 2014) and showed to be better than the alternate 1-factor model (Table 2). Moreover, the fit statistics were consistent with the recent study by Ilyas et al (2021). However, we chose the 3-factor model, as it supports the conceptual and operational definitions of the constructs used for empirical analysis.…”
Section: Confirmatory Factor Analysis (Cfa)supporting
confidence: 56%
“…Satisfied employees contribute to organizational success and performance [ 53 ]. The authors of [ 54 ] found that job satisfaction is associated with leadership and performance, motivation, attitude, and voice behavior [ 55 ]. Therefore, prior studies found factors that can improve the job satisfaction of employees in the workplace.…”
Section: Literature Review and Hypotheses Developmentmentioning
confidence: 99%
“…There have been continuous efforts in the past on the part of researchers to identify the style of leadership that would impact the subordinate’s behavior and attitudes positively [ 14 ]. Previous studies have explored that various styles of leadership have been dominant in an organization, the most prominent being transformational and charismatic styles [ 19 ]. An effective style of leadership is the main source of competitive advantage [ 59 ].…”
Section: Literature Reviewmentioning
confidence: 99%
“…There has been a continuous effort on the part of researchers to identify a style of leadership that better impacts a follower’s behavior and attitudes [ 13 ]. Various leadership styles have been dominant in organizational behavior, the most prominent being transformational and charismatic leadership [ 19 ]. The new dominant theories of leadership styles are authentic, servant, and ethical leadership.…”
Section: Introductionmentioning
confidence: 99%